2020
DOI: 10.1016/j.yclnex.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum folate levels and fatty liver disease

Abstract: s u m m a r yBackground: Non-alcoholic fatty liver disease is one of the most common chronic liver diseases. Due to the lack of definitive documentation for the effect of folic acid on fatty liver, this study was conducted to determine the relationship between serum folate levels and fatty liver in patients referred to Imam Hossain Hospital in Shahroud, in 2016. Methods: This caseecontrol study was performed on 150 patients. The case group was fatty liver patients whose disease was diagnosed based on laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…Earlier studies showed that serum Hcy levels were positively associated with NAFLD, whereas serum B12 and Fol levels were negatively correlated with NAFLD/NASH severity [5][6][7][8]. Here, we showed conclusively that serum Hcy was positively correlated with NASH severity in patients, primates and mice.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Earlier studies showed that serum Hcy levels were positively associated with NAFLD, whereas serum B12 and Fol levels were negatively correlated with NAFLD/NASH severity [5][6][7][8]. Here, we showed conclusively that serum Hcy was positively correlated with NASH severity in patients, primates and mice.…”
Section: Discussionsupporting
confidence: 70%
“…[3,4]. Several recent clinical studies showed that serum Hcy levels were positively associated with NASH, and B12 and Fol levels were negatively correlated with NAFLD/NASH severity [5][6][7][8]. However, it is not known whether HHcy has a pathogenic role in NASH.…”
Section: Introductionmentioning
confidence: 99%
“…Folate undergoes an enterohepatic cycle which is important for the folate homeostasis [32]. In people, folate deficiencies are seen in people with several chronic liver diseases [33,34]. Although serum folate concentrations remained within reference values, a significant increase was found between diagnosis and three months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Çeşitli çalışmalarda serum folik asit seviyelerinin NAYKH hastalarında kontrollere kıyasla anlamlı şekilde düşük olduğu (44) ve düşük folik asit seviyelerinin fibroz derecesi ile ilişkili olduğu bulunmuştur (45). Yüksek yağlı diyet indüklü steatohepatit gelişen ratlarla yapılan bir çalışmada folik asit tedavisinin hepatik hücrelerde PPARα seviyelerini düzenleyerek hepatik lipid metabolizmasını iyileştirdiği, steatoz ve hepatoselüler hasarı hafiflettiği bildirilmiştir (46).…”
Section: Folatunclassified